Frost Durability and Strength of Concrete Prepared with Crushed Sand of Different Characteristics - Ming-kai Zhou; Zhan-ao Liu; Xiao Chen (Advances in Materials Science and Engineering)
The influences of fines content, methylene blue (MB) value, and lithology of crushed sand (CS) on frost durability and strength of concrete were investigated, and the frost durability and strength of crushed sand concrete (CSC) and river sand concrete (RSC) were compared. The results show that inclusion of fines improves CSC compressive strength and reduces frost durability of C30 CSC when fines content reaches 10%, whereas it has little negative influence on frost durability of C60 CSC. Increasing MB value does not negatively affect compressive strength of C30 CSC but decreases compressive strength of C60 CSC and frost durability of CSC, and the reduction is more pronounced when MB value exceeds 1.0. Lithology has no prominent influence on frost durability and compressive strength of CSC within the lithologies (dolomite, limestone, granite, basalt, and quartz) studied. Though compressive strength of CSC is a little higher than RSC under equal water to cement ratio, frost durability of CSC is no better than RSC especially for C30 CSC, and air-entraining agent is suggested for enhancing frost durability of C30 CSC exposed to freezing environment.